THE EFFECT OF EMOTIONAL INTELLIGENCE ON THE UNDERSTANDING LEVEL OF ACCOUNTING (Study at UB Student Accounting Department) - Mardika, I Made Dwi Putra (Jurnal Ilmiah Mahasiswa FEB, 2014)
This research aims to obtain empirical evidence regarding the impact of emotional inteligence on the understanding level of accounting. Emotional intelligence is the ability which someone sets his/her emotional life with his  inteligence, retain his emotional balance and its revelation through a skill of self awareness, self control, self motivation, emphaty and social skill. This research sample comprised 100 undergraduate students of Accounting Department of Brawijaya University Malang by using regression analysis technique. The  sampling  technique used was  purposive sampling,  and  a set of  questionnaire was used to collect the data.    The research result indicate that emotional inteligence consisting of self  introduction, self control, motivation, emphaty and social skill have a significant effect on  the  understanding  level of accounting both partially and simultaneously. Keywords: Emotional inteligence, understanding  level of accounting, undergraduate students of Accounting Department of Brawijaya University Malang.